Vertigo A Clinical Guide - Zaidi, Shabih H.; Sinha, Arun (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Vertigo is an enigma. It is a malady for all ages. It is also a greatly misunderstood and underrated clinical condition. Most physicians see vertiginous patients in their daily practice but no consensus has yet been reached on the true extent of this highly debilitating condition. Vertigo has diverse causes and forms. Diagnosis usually relies heavily on a detailed history and thorough clinical examination, but imaging techniques and a range of vestibular tests are also helpful. Most patients can be treated conservatively with anti-vertiginous drugs and/or rehabilitation therapy, but some require surgical intervention. This monograph on vertigo is based on the personal, hands-on, practical and clinical experience of managing vertigo in a large university-affiliated hospital. It covers all aspects of the subject, offering the latest information on epidemiology, aetiopathogenesis, diagnostics, the battery of vestibular and allied tests, treatment, rehabilitative management and ethical considerations. The neglected but substantial problem of paediatric vertigo is addressed, as are the many pathologies in the elderly population that can lead to disequilibrium and repeated falls. This book will prove of value to a range of practitioners, including family physicians, otologists, audiologists, vestibular scientists, neurologists, paediatricians, geriatricians, physiotherapists, rehabilitation therapists  and general doctors, as well as medical and nursing students.